2017
DOI: 10.1074/jbc.m116.749689
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145 Modulates N6-Methyladenosine Levels by Targeting the 3′-Untranslated mRNA Region of the N6-Methyladenosine Binding YTH Domain Family 2 Protein

Abstract: Edited by Joel Gottesfeld

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
218
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(219 citation statements)
references
References 49 publications
1
218
0
Order By: Relevance
“…YTHDF2 was found to be up‐regulated in HCC, and miR‐145 was identified as an upstream regulatory factor to elevate m 6 A level by targeting YTHDF2 which was consistent with silencing of YTHDF2 78. In addition, YTHDF2 was also found to be significantly up‐regulated in prostate cancer tissues 79.…”
Section: The Dual Role Of M6a Modification In Human Cancerssupporting
confidence: 53%
“…YTHDF2 was found to be up‐regulated in HCC, and miR‐145 was identified as an upstream regulatory factor to elevate m 6 A level by targeting YTHDF2 which was consistent with silencing of YTHDF2 78. In addition, YTHDF2 was also found to be significantly up‐regulated in prostate cancer tissues 79.…”
Section: The Dual Role Of M6a Modification In Human Cancerssupporting
confidence: 53%
“…Most recently, a growing number of studies have reported that methylases and demethylases of m 6 A are correlated with cancer (8,30,38,39). As METTL3 is the core component of m 6 A the methyltransferase complex, we wondered whether SUMOylation of METTL3 is connected with tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of mRNA m 6 A methylation by dot-blotting was performed followed by a published procedure with minor changes (13,30). Briefly, total RNAs were isolated using the Trizol method and mRNAs were isolated by using GenElute™ mRNA Miniprep Kit (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Upon heat shock, YTHDF2 relocates to the nucleus, protects transcripts with m 6 A‐modified 5′UTR from demethylation by FTO and helps in cap‐independent translation initiation during stress conditions . A recent report on hepatocellular carcinoma demonstrated that increased levels of tumor suppressor miR‐145 degrades YTHDF2 and protects m 6 A‐containing RNA species . The contradicting function of these two proteins determines the final outcome of m 6 A targets.…”
Section: Decoders Of the M6a Markmentioning
confidence: 99%